An improvement of the sensitivity of GPS radio occultation data to detect gravity waves through observational and modeling factors. Issue 2 (15th January 2016) - Alexander, P.; de la Torre, A.; Hierro, R.; Llamedo, P.
Abstract: There is a mid-latitude region to the East of the Andes Range in the Southern Hemisphere that exhibits ideal conditions for the generation of gravity waves (GW) by topography mainly during winter. The configuration favors the generation of wavefronts that are parallel to the North–South direction. Global Positioning System (GPS) radio occultation (RO) retrievals from the COSMIC (Constellation Observing System for Meteorology, Ionosphere and Climate) mission exhibit in a large proportion of the soundings an orientation which should be favorable to the detection of these wavefronts. We try to verify if this GW activity surplus on the East with respect to the West in the studied zone in winter emerges clearly in the GPS RO data between years 2007 and 2012. We argue that the orientation of the soundings but also the mathematical model selected to represent the GW energy distribution can affect the possibility of detecting the signatures of the waves. In particular, we explore a new interpretation of the GW energy distribution observed by GPS RO at the lowest values, as they stay below the precision limit of the technique. We suggest to replace that part of the measured distribution by an exponential curve that in general suits the trend of all the other observed energies. In following this alternative it is shown that the calculated mountain wave activity in the studied sector is now even more clearly larger in the East than in the West during winter. Finally, we consider that energy distributions observed with any measurement technique should in general not be considered as the solely contribution from waves, as also other variable phenomena may be adding to the final outcome.